ANALISIS PERBANDINGAN PENGGUNAAN TYPE KANTILEVER DAN GRAFITASI TERHADAP DINDING PENAHAN TANAH PADA INSTALASI PENGELOHAN AIR (IPA) BANTUAS TIRTA KENCANA KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - RAHMANSYAH, IDUL (KURVA S JURNAL MAHASISWA, 2018)
Retaining wall is a construction that serves to hold the soil loose or natural and preventthe collapse of sloping land or slopes whose stbility can’t be guaranteed by the slope of the land it self. Retained soil gives an active impluse to the structure of the wall so that the structure tends tobe rolled and displaced. The water treatment plants (IPA) Bantuas Tirta Kencana, the to avoid landslides, the soil shifts or collapses in the area, it’s necessary to build a retaining wall. The water treatment plants (IPA) Bantuas Tirta Kencana located in a location far from residential areas, because of it’s position arround the forest area, the location of the building is at’n altitude of +15 m from the main road. In addition to avoiding landslides, sliding, and collapsing also because the istalasi Bantuas is a public facility and a large-scale treatment plant. The method used for retrieving land data using boring and sondir data and laboratory data that support this research and carried out in the field. While the analysis method for handling the stability of shear, roll nd collapse using rankine and coulomb method on cantilever type and gravity type retaining walls. From the result of the calculations, it was concluded that the retaining wall heigh was 5,2 m and the width was 3,5 m and the lenght of the segmenting was 20 m. Stability of retaining wall cantilever type method rankine against bolster 2,933 ≥ 2 (safe ), shear 2,397 ≥ 2 ( safe ), and collapse 26,74 ≥ 3 ( safe). Whereas in the coulomb method against bolster 3,252 ≥ 2 (safe ), shear 2,650 ≥ 2 ( safe ), and collapse 27,951 ≥ 3 ( safe). Stability of retaining grafity type method rankine against bolster 1,760 ≥ 2 (no safe ), shear 1,609 ≥ 2 ( no safe ), and collapse 14,366 ≥ 3 ( safe). Whereas in the coulomb method against bolster 1,947 ≥ 2 (no safe ), shear 1,806 ≥ 2 ( no safe ), and collapse 16,185 ≥ 3 ( safe).